2022
DOI: 10.1007/s11524-022-00624-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective Places: the Relationship between Neighborhood Quality and Preterm Births to Black Women in Oakland, California (2007–2011)

Abstract: Black women have the highest incidence of preterm birth (PTB). Upstream factors, including neighborhood context, may be key drivers of this increased risk. This study assessed the relationship between neighborhood quality, defined by the Healthy Places Index, and PTB among Black women who lived in Oakland, California, and gave birth between 2007 and 2011 (N = 5418 women, N = 107 census tracts). We found that, compared with those living in lower quality neighborhoods, women living in higher quality neighborhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
0
3
0
1
Order By: Relevance
“…Prior research has identified communities with lower composite health index scores as those with increased barriers to accessing health care resources and worse health outcomes. 12,14,15 Our study demonstrates that these trends hold true, as women residing in areas with lower composite health index scores were less likely to undergo fertility-sparing treatment or ART. Tools such as the California Healthy Places Index can help target program interventions to the communities with the most need.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Prior research has identified communities with lower composite health index scores as those with increased barriers to accessing health care resources and worse health outcomes. 12,14,15 Our study demonstrates that these trends hold true, as women residing in areas with lower composite health index scores were less likely to undergo fertility-sparing treatment or ART. Tools such as the California Healthy Places Index can help target program interventions to the communities with the most need.…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, prior research has found associations between lower composite health of an individual's community (as measured by community health indices), decreased access to health services, and worse health outcomes. [12][13][14][15] Notably, none of these studies have evaluated the association between geospatial and health indices and fertility-sparing treatment and ART among survivors of breast and gynecologic cancers.…”
mentioning
confidence: 99%
“…8,9,11 There is increasing appreciation of how neighborhood conditions and community factors influence PTB. [12][13][14][15][16][17] Poverty, 18 air pollution, 19,20 and composite measures of neighborhood quality 21 are associated with PTB. Communities reflect a complex amalgamation of risk and protective factors.…”
Section: Introductionmentioning
confidence: 99%
“…La estimación adecuada de la edad gestacional (EG) es fundamental para evitar decisiones obstétricas y perinatales erróneas (1). Los cálculos de la EG por la fecha de última menstruación (FUM) pueden estar sesgados, ya que el momento de ovulación varía desde el punto de vista fisiológico (2). Además, la capacidad de recuerdo de las mujeres también modifica la fiabilidad del cálculo (3).…”
Section: Introductionunclassified